RESTORATIVE JUSTICE: THE DILEMMA OF LEGAL CERTAINTY AMIDST SECTORAL REGULATORY BARRIERS OF LAW ENFORCEMENT AGENCIES - Ann Eko Widiarto; Nyoman Nurjana; Yolenta Lobe Liko (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The main problem with the implementation of restorative justice in Indonesia is that it is still regulated sectorally by the Police, the Prosecutor's Office, and the Courts, resulting in a lack of synchronization, overlapping norms, and the potential for legal uncertainty. Through normative juridical research with a statutory, conceptual, and case-based approach, this article examines the differences in the regulation and implementation of restorative justice in National Police Regulation Number 8 of 2021, Attorney General Regulation Number 15 of 2020, and Supreme Court Regulation Number 1 of 2024. The results show that regulations at the investigation level still contain vague and immeasurable formulations, while the Prosecutor's Office has clearer criteria but remains inconsistent with the Supreme Court Regulation, which even allows certain recidivists to seek restorative resolution. At the court level, restorative justice functions only as an approach without terminating the case process, thus differing in orientation from the two previous levels. These differences create inconsistencies in implementation, confusion of authority, and diminish the essence of restorative justice as a restorative instrument. This article emphasizes the need for short-term regulatory harmonization and the establishment of a specific law on restorative justice as an integrated legal umbrella to ensure legal certainty, justice, and benefit for all parties involved in the criminal justice process.